2017
DOI: 10.1080/09168451.2016.1240604
|View full text |Cite
|
Sign up to set email alerts
|

Choline and betaine ameliorate liver lipid accumulation induced by vitamin B6 deficiency in rats

Abstract: We investigated the efficacy of supplementing the diet with choline or betaine in ameliorating lipid accumulation induced by vitamin B (B) deficiency in rat liver. Male Wistar rats were fed a control, B-deficient, choline-supplemented (2, 4, or 6 g choline bitartrate/kg diet) B-deficient diet or betaine-supplemented (1, 2, or 4 g betaine anhydrous/kg diet) B-deficient diet for 35 d; all diets contained 9 g L-methionine (Met)/kg diet. Choline or betaine supplementation attenuated liver lipid deposition and rest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…Experimental studies have proved that choline deficiency might cause varying degrees of liver diseases ranging from dyslipidemia to liver cancer 27 , whereas choline or betaine supplementation could ameliorate liver damage 15,16 . Second, though choline is essential for maintaining normal liver function, its functions are more than this.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies have proved that choline deficiency might cause varying degrees of liver diseases ranging from dyslipidemia to liver cancer 27 , whereas choline or betaine supplementation could ameliorate liver damage 15,16 . Second, though choline is essential for maintaining normal liver function, its functions are more than this.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, choline is a major source of methyl groups via oxidation to betaine, their functions involving the re-methylation of homocysteine to methionine are critical for DNA and histone methylation homeostasis, and therefore have been reported to be associated with cancer risk 2 (including liver cancer) and survival [7][8][9][10] . Experimental studies have reported that when deprived of choline, varying degrees of liver damages and liver diseases developed, including elevated transaminases 11 , affected lipid metabolism and transport 12 , fatty liver 13 , liver cirrhosis 13 and even liver cancer 14 , whereas choline or betaine supplementation ameliorated liver damage 15,16 , and choline supplementation increased global DNA methylation and DNA methyltransferase expression in HepG2 cells 17 , which implied that choline or betaine might not only be associated with hepatocarcinogenesis, but also with liver cancer survival. To date, although scarcely, three case control studies [18][19][20] have evaluated the relationship between choline/betaine and human liver cancer risk, in which consistently favorable effects of choline were found.…”
Section: Introductionmentioning
confidence: 99%
“…Liver is among the first organs to accumulate choline absorbed from the intestine and responsible for most of choline metabolism [26]. Experimental studies have proved that choline deficiency might cause varying degrees of liver diseases ranging from dyslipidemia to liver cancer [26], whereas choline or betaine supplementation could ameliorate liver damage [15,16]. Second, though choline is essential for maintaining normal liver function, its functions are more than this.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly, choline is a major source of methyl groups via oxidation to betaine, their functions involving the re-methylation of homocysteine to methionine are critical for DNA and histone methylation homeostasis, and therefore have been reported to be associated with cancer risk [2] (including liver cancer) and survival [7][8][9][10]. Experimental studies have reported that when deprived of choline, varying degrees of liver damage and liver diseases developed, including elevated transaminases [11], affected lipid metabolism and transport [12], fatty liver [13], liver cirrhosis [13] and even liver cancer [14], whereas choline or betaine supplementation ameliorated liver damage [15,16], and choline supplementation increased global DNA methylation and DNA methyltransferase expression in HepG2 cells [17], which implied that choline or betaine might not only be associated with hepatocarcinogenesis, but also with liver cancer survival. To date, although scarcely, three case control studies [18][19][20] have evaluated the relationship between choline and betaine and human liver cancer risk, in which consistently favorable effects of choline were found.…”
Section: Introductionmentioning
confidence: 99%
“…We previously revealed that PC, choline, and betaine ameliorate liver lipid accumulation in rats fed a 0.9% Met-supplemented B6-deficient diet (2,3). Choline and betaine are anti-obesity factors (16)(17)(18)(19) linked to Met metabolism, and betaine is produced by choline oxidation (20).…”
mentioning
confidence: 99%